Pemanfaatan ICT dalam Meningkatkan Motivasi Peserta Didik pada Pembelajaran Pendidikan Islam di Sekolah Dasar - Saputri, Juwita; Damayanti, Latipia; Luthfiah, Qonita; Kiska, Nurul Delima; Sherlyna, Sherlyna (Khalifa Journal of Islamic Education, 2021)
The purpose of this research was to analyze how the response and effectiveness of learning media using 'Kahoot!' technology in motivating students' learning in elementary schools. This study uses a quantitative method with the type of correlation, the data is taken through a questionnaire to thirty respondents from one elementary school with a total sampling technique. All data were analyzed descriptively and inferentially using SPSS 20 software. Overall, the results of the analysis show that i) the use of learning media through Kahoot! Getting a very good response from students, ii) the use of Kahoot! also has an impact in motivating students in learning, with the results of a correlation analysis of 0.756. This means that there is a positive relationship between the use of media and students' learning motivation. The results of this study have shown that the use of technology media has proven to be effective and has succeeded in increasing students' responses and learning motivation. In fact, teachers need to improve their competence related to the use of ICT as a medium in learning, so that they are able to integrate ICT into learning materials.Â